Tipologi Rumah Masyarakat Menengah Bawah Di Pulau Jawa - Adamy, Aulina; Maharani, Lisa; Aini, Qurratul; Meillyta, Meillyta; Pazeth, Naufal Sulthana (Jurnal RAUT, 2024)
Low-cost houses occupied by the middle to lower economic class make up the majority in Indonesia, especially on the island of Java with the biggest population. This type of house generally does not involve architects and civil engineering to keep it affordable. The purpose of this study is to understand this type of houses in Java Island through architectural history timelines and typology analysis as the methodology. This study covers three provinces: West, Central and East Java. Two special regions, namely Jakarta and Yogyakarta, are excluded in this study and will need a specific study in the future. Vernacular houses are excluded too because they require special analysis. As a result, this study produced four groups: brick walls with clay tile roofs; brick walls with tin roof; wood/bamboo walls with clay tile roofs; wooden/bamboo walls with tin roofs. While, thatched roofs and stilt houses are considered closer to the vernacular. Usually, these houses are grounded and self-built (without the help of architects or civil engineering experts). Or built by developers for subsidy schemes. Based on timeline analysis, all of these simple houses can be in the form of post-independence architecture to the contemporary era.